Complementarities of R&D strategies on innovation performance: Evidence from Taiwanese manufacturing firms - Lin, Eric S.; Hsiao, Yi-Chi; Lin, Hui-lin (Technological and Economic Development of Economy, 2014)
This paper aims to empirically test the R&D complementarities among three alternative R&D strategies, namely, internal R&D, external R&D and cooperative R&D, under different measures of innovation output. Using a firm-level data set based on the Taiwanese innovation survey (in accordance with CIS 3) conducted in 2003, we are able to compare the R&D activities in this newly-industrialized country with other developed countries. Additionally, we apply a two-step procedure to reduce the endogeneity problem caused by the firms’ choices of strategies to obtain consistent estimators, which can be regarded as a combined method of adoption and productivity approaches. We show that the results of the estimation for R&D complementarities may be biased upwards or downwards if we do not include selection equations in the empirical models, thereby giving rise to endogeneity problems. Our empirical results generally support the existence of R&D complementarities, while the strength of complementary effects may vary across different measures of innovation output. Moreover, our finding suggests that the complementary relationship between external and cooperative R&D is fairly robust to various model specifications.